Primary prevention of asthma and atopy during childhood by allergen avoidance in infancy: a randomised controlled study. Issue 6 (1st June 2003) - Arshad, S H; Bateman, B; Matthews, S M
Abstract : Background: Recent increases in the prevalence of asthma and atopy emphasise the need for devising effective methods for primary prevention in children at high risk of atopy. Method: A birth cohort of genetically at risk infants was recruited in 1990 to a randomised controlled study. Allergen avoidance measures were instituted from birth in the prophylactic group (n=58). Infants were either breast fed with mother on a low allergen diet or given an extensively hydrolysed formula. Exposure to house dust mite was reduced by the use of an acaricide and mattress covers. The control group (n=62) followed standard advice as normally given by the health visitors. At age 8, all 120 children completed a questionnaire and 110 (92%) had all assessments (skin prick test, spirometry, and bronchial challenges). Results: In the prophylactic group eight children (13.8%) had current wheeze compared with 17 (27.4%) in the control group (p=0.08). Respective figures were eight (13.8%) and 20 (32.3%) for nocturnal cough (p=0.02) and 11 of 55 (20.0%) and 29 of 62 (46.8%) for atopy (p=0.003). After adjusting for confounding variables, the prophylactic group was found to be at a significantly reduced risk for current wheeze (odds ratio (OR) 0.26 (95% confidence interval (CI) 0.07 to 0.96)), nocturnal cough (OR 0.22 (95% CI 0.06 to 0.83)), asthma as defined by wheeze and bronchial hyperresponsiveness (OR 0.11 (95% CI 0.01 to 1.02)), and atopy (OR 0.21 (95% CI 0.07 to 0.62)). Conclusion: Strict allergen avoidance in infancy in high risk children reduces the development of allergic sensitisation to house dust mite. Our results suggest that this may prevent some cases of childhood asthma.